Collective public transport under the logic of the capitalist production of space: an analysis of the bus service in the Metropolitan Region of Recife - Silva, Marília do Nascimento; Lapa, Tomás de Albuquerque (Pontifícia Universidade Católica de São Paulo, 2019)
In today's urban societies, the growth of the State's role coexists with the privatization process of the services provided by this apparatus. The traditional justification lies in the search for greater competitiveness and efficiency in the services provided. The State has been increasingly indispensable in the mediation between private and collective interests; however, in the case of collective public transport in the Brazilian context, the logic that constituted it as an essential service exempts it from the public responsibility that belongs to it, opening windows for a discussion about the dynamics of the management and operation of this equipment. This article analyzes collective public transport in the Metropolitan Region of Recife in the perspective of the capitalist production of space.